The Role of Rural and Urban Land and Building Tax Through Effectiveness and Contribution to Local Revenue (Case Study in Air Salemba Village, Pangkalpinang City) - Putra, Agung Rizki; Armeta, Ayu; Oktavia, Winda; Triana, Dita (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2024)
The purpose of this research is to analyze the level of effectiveness and contribution of the role of rural and urban land and building tax in Air Salemba Village. This research uses descriptive quantitative methods. Descriptive method is a research method that serves to provide an overview or description of the object under study through data or samples that have been collected, without analyzing and making conclusions that apply to the public. The data used in this study are mixed data, namely primary data obtained from Air Salemba Village related to the realization of revenue and the target of rural and urban land and building tax revenue. As for secondary data obtained from data from the central statistics agency, reports, journals, and other sources related to the realization of PAD revenue. The results showed that the effectiveness and contribution of PBB-P2 to PAD in Air Salemba Village, Pangkalpinang City in 2022, can be concluded that the level of effectiveness is categorized as less effective. Although, the level of effectiveness is categorized in effective criteria because the realization of revenue is in accordance with the predetermined revenue target. The level of PBB-P2 contribution to PAD is still categorized as less. Air Salemba Village is one of the highest PBB-2 tax revenues in Gabek Sub-district but its contribution to PAD is not significant.